The Influence of Religious Guidance on Adolescent Emotional Control at the Pekanbaru Class II Children's Special Development Institute (Jurnal Bimbingan dan Konseling Islam, 2022)
The study discussed the effect that religious guidance can have on the emotional control of a teenager at the new ape-class ii coaching institute. As for the purpose of this study, it is to know if there is any influence relegious guidance on the emotional control of a teenager at the new apresidency institute for the development of a new class ii student. As for research using quantitative descriptive methods.The total population is 30 while the sample of this study uses the Total Sampling technique, which is as many as 30 respondents. Data collection techniques in this study using questionnaires, observation and documentation. Data were analyzed using SPSS (Statistical Product and Service Solution) 18 program with simple linear regression analysis. With this the results of the study indicate that religious guidance has an effect on adolescent emotional control in the Special Class II Children's Guidance Institute Pekanbaru. Based on the results of Simple Linear Regression analysis, the probability level of sig.(2-tailed) is 0.00, and the probability value is 0.05. So it can be concluded that the probability value is 0.05> 0.00 then Ho is rejected and Ha is accepted, meaning that it is significant. which shows that there is a significant influence between Religious Guidance on Adolescent Emotion Control at the Special Class II Child Development Institute Pekanbaru. with a percentage of 77.4.%